Double-entry bookkeeping and balance of payments: the need for developing a new approach - Edoardo Beretta; Alvaro Cencini (Insights into Regional Development)
On the basis of the identity between each country’s global imports (commercial and financial) and exports (commercial and financial), which is one of the fundamental economic principles of the balance of payments, the paper highlights why and how the leading account of transactions from/to the rest of the world needs to be reformed. As a strategic goal, the balance of payments should finally move beyond its current purely statistical and simple-entry bookkeeping approach in order to improve its macroeconomic relevance. This would also imply a new way of carrying out cross-border payments, which could in turn pave the way for a new system of international payments. The development of an economic account of the nation as a whole and the introduction of a consistent way of recording transactions following a truly double-entry bookkeeping would also erase statistical discrepancies ex ante and reflect the necessary equality (identity) of credits and debits both for all transactions taken together and for each of them separately. The balance of payments is already a powerful economic tool, but only through a money-consistent reform would it display its full potential.